(untitled) (Revista Contexto & Saúde, 2022)
The aim of the present study was to verify the prevalence and factors associated with negative self-perceived health in the elderly assisted by primary care. An observational, cross-sectional analytical study was carried out with 241 elderly people from a community in Vitória, Espírito Santo. Self-perceived health was the outcome variable, and sociodemographic characteristics, lifestyle and health characteristics were the exposure variables. Data were analyzed using Pearson’s Chi-Square test and the Prevalence Ratio was calculated for variables significantly associated with the outcome (p <0.05). The prevalence of negative self-perceived health was 46.5%, and the factors associated with this outcome were: white race, polypharmacy, incapacity for daily activities, depressive symptoms, risk of falls and negative perception of quality of life. The findings of this study can assist in the management of care provided to the elderly, aiming at maintaining and recovering the independence, autonomy and health of the elderly, and thus contribute to a better quality of life for this population.